Variations in growth, physiology and fodder quality among salicornia persica ecotypes irrigated with persian gulf seawater - Yazdan Izadi; Majid Nabipour; Gholamhassan Ranjbar (Scientific Reports)
Abstract Fodder production in saline environments requires salt-tolerant plants. This study investigated the potential of the halophyte Salicornia persica ecotypes as a fodder crop under seawater salinity by examining its physiological and biochemical responses. The effects of varying salinity levels [control (0.96 dS.m−1), and 10, 20, and 40 dS.m−1, achieved by diluting Persian Gulf water] on growth, yield, stomatal exchange rate, photosynthetic traits, and qualitative fodder characteristics were evaluated. Three S. persica accessions collected in Iran (Central Plateau, Urmia, and Bushehr) were included. The results showed that, among the tested ecotypes, Central Plateau and Urmia exhibited the most desirable interaction with the 10 dS.m−1 salinity treatment, highlighting a beneficial combination of ecotype and salinity level. Regarding growth characteristics, plant height and forage yield were highest at 10 dS.m−1 and lowest at 40 dS.m−1 salinity. In terms of forage quality, the Bushehr accession under non-stress conditions and the Central Plateau accession at 20 dS.m−1 exhibited the highest nitrogen and crude protein percentages. The 10 and 20 dS.m−1 salinity treatments displayed more favorable forage quality profiles, whereas the 40 dS.m−1 treatment resulted in elevated fiber and Acid Detergent Fiber (ADF) percentages, potentially reduces fodder palatability for livestock. These findings suggest that the Central Plateau and Urmia ecotypes demonstrate significant potential for forage production in saline environments. These ecotypes are a promising option for cultivation in coastal areas, particularly with irrigation using Persian Gulf seawater at a salinity of 10–20 dS.m−1.